FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NONKEUANGAN - Della Mayrenza; Suryanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to get an empirical evidence about factors that influence firm value. Independent variables used in this research are leverage, liquidity, profitability, firm size, investment policy, activity, dividend policy, firm growth, institutional ownership, and managerial ownership. The objects of this research are nonfinancial companies listed in Indonesia Stock Exchange (IDX) from the period of 2015 to 2017. This research used 66 companies as samples and samples selected using purposive sampling method. Data were analyzed using multiple regression method. In this research, firm value were measured by PBV (Price to Book Value). The result of this research indicates that leverage, profitability, investment policy, institutional ownership, and managerial ownership have influence toward firm value. While liquidity, firm size, activity, dividend policy, and firm growth have no influence toward firm value.